El Excentrico, 1969-01-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
January 5, 1969 [5 de enero de 1969]. No volume or issue number. Cover has a New Year's message from the Furniture Discount House that reads, ."..a most Prosperous and Happiest of New Year's."